2020
DOI: 10.1002/em.22376
|View full text |Cite
|
Sign up to set email alerts
|

Clothianidin induces DNA damage and oxidative stress in bronchial epithelial cells

Abstract: Clothianidin (CHN) is a member of the neonicotinoid group of insecticides. Its oxidative and DNA damage potential for human lung cells are not known. Therefore, the present study was designed to examine the effects of CHN on DNA damage and oxidative stress in human bronchial epithelial cells (BEAS‐2B) treated with CHN for 24, 72, and 120 hr. Our results indicate that CHN decreased cell viability in a concentration‐dependent manner. CHN induced DNA single‐strand breaks because alkaline comet parameters such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Of note, several studies additional to the regulatory studies mentioned in the Results section of this paper have been published regarding the genotoxic potential of CTD. No significant effect towards the Comet assay was observed in HepG2 human hepatoma cells, while CTD induced increase in tail intensity in neuronal SHSY-5Y and bronchial epithelial BEAS-2B cells ( Atli Sekeroglu et al, 2020 ; Senyildiz et al, 2018 ). Additionally, CTD induced the formation of DNA double strand breaks in BEAS-2B cells as evidenced by the increase in phosphorylated H2AX protein ( Atli Sekeroglu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 87%
“…Of note, several studies additional to the regulatory studies mentioned in the Results section of this paper have been published regarding the genotoxic potential of CTD. No significant effect towards the Comet assay was observed in HepG2 human hepatoma cells, while CTD induced increase in tail intensity in neuronal SHSY-5Y and bronchial epithelial BEAS-2B cells ( Atli Sekeroglu et al, 2020 ; Senyildiz et al, 2018 ). Additionally, CTD induced the formation of DNA double strand breaks in BEAS-2B cells as evidenced by the increase in phosphorylated H2AX protein ( Atli Sekeroglu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 87%
“…After formation of DNA DSBs, H2AX is phosphorylated and gH2AX occurs in response to DNA damage. 53BP1, a well‐known DNA damage response protein, then binds to DSBs sites (Atlı Şekeroğlu et al ., 2020). Our neutral comet and immunofluorescence results of gH2AX and 53BP1 foci clearly showed that PIO induced DNA DSBs formation.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were treated with eight concentrations of PIO (1, 2.5, 5, 10, 25, 50, 100, and 250 μM) for 24, 48, and 72 hr. MTT assay was performed as previously published (Atlı Şekeroğlu at el., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations